Pengaruh Sistem Komunikasi, Kepemimpinan dan Pengambilan Keputusan Terhadap Kepuasan Kerja Guru Pondok Pesantren - Afriansyah Afriansyah; Andi Rusada Sitorus; Asiah Lubis; Ira Anggreni; Yuly Maryani Lubis; Hasrita Lubis (Forum Kerjasama Pendidikan Tinggi, 2022)
The formulation of the problem in this study is whether the communication, leadership and decision-making systems simultaneously have a positive and significant effect on the job satisfaction of the teachers of Pondok Pesantren Bina Ulama Kisaran. This study aims to determine the effect of communication, leadership and decision-making systems on job satisfaction of teachers at the Kisaran Islamic Boarding School Bina Ulama. The sample in this study were all 36 teachers of the Kisaran Islamic Boarding School Bina Ulama. The data analysis technique in this research is Multiple Linear Regression. The results of this study indicate that the communication system partially has a positive but not significant effect on job satisfaction; Leadership partially has a positive and significant effect on job satisfaction; Decision making partially has a positive and significant effect on job satisfaction; The communication system, leadership and decision making simultaneously have a positive and significant effect on job satisfaction.